(untitled) (Journal of the College of Basic Education, 2023)
This research deals with conducting an original study of a new term, which is (moral reasoning), and it is a concept derived from (good reasoning), due to its compatibility with the nature of modern poetry, whose contexts are characterized by ambiguity and strangeness, especially the explanatory context in which the reason is vague and the reasoning is more ambiguous. Therefore, the study determined the linguistic meaning And the terminology of the concept (moral reasoning) and the reasons that led to its selection and then its application to poetry. In addition, I tried to study the concept in terms of its sound ripples and its relationship to the context and its relationships in modern Arabic poetry.